Productive Restructuring: Impacts On the “Social Issue” (Research, Society and Development, 2020)
The present article has as theme the repercussions of the metamorphoses in the world of work. We will discuss how changes in the process of capital production bring consequences for workers, causing the expansion of unemployment, of poverty, of hunger, of social inequality, among other factors. Like this, we watch as the process of productive restructuring intensif the "social issue" in contemporary society. Thus, the research objective is to discuss the negative contributions caused by metamorphoses in the lives of employees. To follow this path, we decided to check how subjects are affected in the area of job by technological advances, a predominant factor to increase inequalities between service providers. Therefore, a research was carried out qualitative, of character exploratory, from bibliographic survey about metamorphoses occurred in the process of capital production. The said study it's grounded in theoretical presuppositions referring to the repercussions of metamorphoses in the world of work. Within the logic of toyotism, the capture of workers' subjectivity by capital is able to promote a new way of rationalizing work, causing the deregulation of employment,intensifying the levels of exploitation of workers, through multipurpose, multifunctional, precarious, outsourced jobs, perpetuating the various expressions of the “social issue”, such as: poverty, hunger, informal jobs and the lack of access to quality health and education. At the end of the study, we realized that the productive restructuring brought several impacts to the world of work and to wage earners.